(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-170-175 The authors consider the methodological possibilities of working with the word and text as units of language and culture in Russian language lessons and substantiate the idea of the need to create a methodological tool that allows comprehending the word and text as linguistic and cultural units in the relationship. The authors propose to define and build the logic of immersion of the student in culture through the systematic implementation of two mutually dependent directions in working with the word and text as linguistic and cultural units in the study of the school course of the Russian language ("from word to text" and "from text to word"). The interrelated understanding of the word and text as integral units of language and culture should be organized in the process of studying the entire school course of the Russian language, especially when studying vocabulary, morphology, syntax. Keywords: methodology of teaching the Russian language, word, text, linguistic and cultural unit